2016
DOI: 10.1371/journal.pbio.1002517
|View full text |Cite
|
Sign up to set email alerts
|

Host Gut Motility Promotes Competitive Exclusion within a Model Intestinal Microbiota

Abstract: The gut microbiota is a complex consortium of microorganisms with the ability to influence important aspects of host health and development. Harnessing this “microbial organ” for biomedical applications requires clarifying the degree to which host and bacterial factors act alone or in combination to govern the stability of specific lineages. To address this issue, we combined bacteriological manipulation and light sheet fluorescence microscopy to monitor the dynamics of a defined two-species microbiota within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
241
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(265 citation statements)
references
References 64 publications
24
241
0
Order By: Relevance
“…While successful invasions are often attributed to fitness and niche differences [25], unsuccessful invasions are additionally attributed to temporal and spatial environmental variation [26] and probabilistic establishment [14, 20, 27]. Thus, the success of an invasion depends upon the invader, the environment, and chance.…”
Section: Discussionmentioning
confidence: 99%
“…While successful invasions are often attributed to fitness and niche differences [25], unsuccessful invasions are additionally attributed to temporal and spatial environmental variation [26] and probabilistic establishment [14, 20, 27]. Thus, the success of an invasion depends upon the invader, the environment, and chance.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution in vivo imaging of gnotobiotic zebrafish colonized with defined communities of fluorescently labeled bacteria has revealed complex behaviors and spatial organization within the intestinal lumen (Jemielita et al, 2014; Rawls et al, 2007; Stephens et al, 2015), and identified host intestinal motility as an important factor governing microbiota composition (Wiles et al, 2016). Initial comparisons of germ-free zebrafish to those colonized with conventional microbiota revealed diverse roles for microbiota on host physiology (Bates et al, 2006; Rawls et al, 2004).…”
Section: The Pathophysiological Zebrafishmentioning
confidence: 99%
“…In some cases, generic bacterial products, such as lipopolysaccharide are sufficient to mediate microbiota effects, whereas in other cases microbial signals are more specific to particular bacterial lineages (Bates et al, 2006; Rawls, Mahowald, Ley, & Gordon, 2006). We have also demonstrated that the host modulates bacterial dynamics and competition within the intestine (Jemielita et al, 2014; Rawls, Mahowald, Goodman, Trent, & Gordon, 2007; Taormina et al, 2012; Wiles et al, 2016) and that gnoto-biotic zebrafish can be used to identify determinants of microbial colonization, including diet (Semova et al, 2012; Stephens et al, 2015; Wong et al, 2015). Gnotobiotic zebrafish have also been used to study colonization resistance against pathogens (Rendueles et al, 2012).…”
Section: Introductionmentioning
confidence: 99%